Eksplorasi Locus of Control Pada Mahasiswa Fakultas Ekonomi Program Studi Manajemen yang Menghadapi Stres Penyelesaian Tugas Akhir Skripsi - Taaha, Yulian Rinawaty; Walenta, Abdi Sakti; Jualiana, Sanny Feria (Fakultas Ekonomi Universitas KristenTentena, 2025)
This qualitative study explores the role of locus of control (LoC) in managing academic stress among students of the Faculty of Economics, Management Study Program, particularly in completing their final thesis. Using a library research approach, the study analyzes existing literature to understand how LoC influences students’ ability to cope with stress during the thesis-writing process. Findings reveal that students with an internal LoC tend to experience less stress as they believe they have control over their academic outcomes. In contrast, students with an external LoC are more likely to feel helpless, leading to increased stress. The study also emphasizes the importance of supportive environments, such as social support and academic culture, in strengthening internal LoC, which in turn helps students manage stress more effectively. The findings suggest that improving internal LoC in students through academic programs and support systems can enhance their ability to manage academic stress and succeed in completing their thesis.